Os impactos da pandemia do COVID-19 no cotidiano de crianças e adolescentes com Transtorno do Espectro Autista - Cardoso, Gabriela Pissante (Universidade Federal de São Carlos, 2023)
In the context of the COVID-19 pandemic, where emergency strategies were implemented to face and contain the disease, it is essential to understand how some social groups most experienced this moment and dealt with the consequences of this atypical scenario. Thus, the objective of the present study was to identify the impacts of COVID-19 on the daily lives of children and adolescents with Autistic Spectrum Disorder (ASD), from the perspective of families. In addition, the specific objectives were: Understand the possibilities, difficulties and daily challenges experienced by this population during the pandemic; investigate the impacts of the pandemic on the clinical picture of ASD; identify which strategies were adopted by family members to face the difficulties experienced; understand how the return to face-to-face activities has been with the improvement of the pandemic scenario and the easing of security and protection measures. Therefore, an exploratory, descriptive study with a qualitative approach was carried out. The participants were those responsible for children and adolescents with ASD, linked to the occupational therapy service in a medium-complexity outpatient clinic in a medium-sized city in the interior of the State of São Paulo. Data collection was carried out using a characterization form for the participants and also a semi-structured interview with those responsible for the children and adolescents. Among the results, it is highlighted that the pandemic brought implications in the clinical picture and in the individual aspects of the child/adolescent. As much as some children had a good adaptability in this period, changes in behavioral and emotional aspects were mentioned, such as increased crying, constant agitation, increased motor stereotypes and difficulty sleeping without the help of medication, as well as increased anxiety, irritability and anger. The change in routine, due to the security measures adopted, were also identified as challenges of this atypical moment, with the importance of support from education and health professionals being reported for the better well-being of the child/adolescent in the period of isolation and also in the return to face-to-face activities. It is hoped that this study will contribute to a greater understanding of the difficulties experienced in the pandemic scenario in order to enable new reflections and discussions about intervention strategies and public policies aimed at this population.
The effects of the COVID-19 pandemic on the daily lives of children and adolescents with Autistic Spectrum
Keywords: Transtorno do espectro autista; Infecções por coronavírus; Criança; Adolesente; CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA